REVIEW OF DEPRESSION AND ITS RESEARCH STUDIES IN MALAYSIA - Chan Siaw Leng; Fonny Dameaty Hutagalung; Lau Poh Li, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Depression is a common but serious illness that should not be overlooked due to its morbidity and burden. This paper provides a review of the literature on depression and emphasises some important issues of the condition. The studies were identified using electronic databases, yielding a review on key issues like definition, symptoms, outcomes and treatments of depression, and its research studies in Malaysia. Findings revealed that recent studies have started to focus on both physical and psychological symptoms of depression, its impairment in functional well-being, as well as common treatments ranging from biomedical to psychological and psychoanalytic approaches. Thus far, a very limited research has been conducted concerning major depressive adults’ healing experiences and, to a lesser extent, young people. Further exploration is urgently needed to close the considerable research gap.